Mary Richmond in the perspective of Social Work in Spain - Barriga Muñoz, Lourdes; Martínez Alonso, María Ángeles (Cuadernos de Trabajo Social, 2011)
Our personal experience has shown that, although nobody questions that Mary Richmond received a Ph.D. Honoris Causa «for having set the scientific bases of a new profession», (ours) such scientific bases still remain unknown, due to never having been taught as such and due to the lack of theoretical production aimed at refuting, developing or, at least, transmitting them without tergiversation. In this article, we try to present just some quick brush strokes of those scientific bases, mainly because we are conscious of the fact that, in our country, our profession is being rapidly devaluated from many standpoints, identifying it only with resource management and social control and, in the current situation in which social theory finds itself, appearing to have no possibility of modifying that trend. It would be easy to state that the solution would be simply to recover Mary Richmond’s works, but it is not as simple as that since conceptions, ideology, perspectives and finally, the ways of conceiving the present social reality are opposed to those underlying those works. So, we believe that we need an unencumbered view, independent of social sciences, to rediscover our origins, in which we really were a profession, a social discipline with its own know-how and its own way of working, and not just an office to receive those who request an appointment. On the contrary, we aim to influence other sciences, enrich them and demonstrate that social work is a profession necessary to humanity.